2015
DOI: 10.1120/jacmp.v16i2.5218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience using a video‐guided spirometry system for deep inhalation breath‐hold radiotherapy of left‐sided breast cancer

Abstract: The purpose was to report clinical experience of a video‐guided spirometry system in applying deep inhalation breath‐hold (DIBH) radiotherapy for left‐sided breast cancer, and to study the systematic and random uncertainties, intra‐ and interfraction motion and impact on cardiac dose associated with DIBH. The data from 28 left‐sided breast cancer patients treated with spirometer‐guided DIBH radiation were studied. Dosimetric comparisons between free‐breathing (FB) and DIBH plans were performed. The distance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“… and Yang et al. , which both use x‐ray monitoring of left‐sided DIBH. The use of surface imaging in this study achieved a comparable setup margin to those in aforementioned peer works.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… and Yang et al. , which both use x‐ray monitoring of left‐sided DIBH. The use of surface imaging in this study achieved a comparable setup margin to those in aforementioned peer works.…”
Section: Resultsmentioning
confidence: 99%
“…Image guidance is frequently used to detect large setup errors and refine patient positioning in the setting of radiotherapy . Modalities such as electronic portal imaging devices, cone‐beam CT (CBCT), and surface imaging have been implemented to verify setup accuracy of DIBH patients . However, daily shifts in patient setup are inevitable even with image guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Mean heart shifts of 13 mm between FB and DIBH in the μ direction have been previously reported. (8) Therefore, the expected change in MHD between FB and DIBH is on the order of 10 mm. The clinical implications of a small portion of the heart entering the primary beam as measured on a cine image are unknown; (5) however, we found that larger (> 10 mm) in-treatment MHD measurements were uncommon, and were most likely in patients where a portion of the heart was planned in the field.…”
Section: Discussionmentioning
confidence: 99%
“…MHD measurements on the DRRs were consistently smaller than in the cine images due to known differences between heart identification in projected CT contours and the pericardial shadow on MV portal images. (8) For this reason, planned and treatment MHDs were not directly compared, except in examining the correlation between CW positioning errors and MHD differences from planning. We found that chest wall displacement from the planned position was not predictive of increased MHD during treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation